1995
DOI: 10.1515/znc-1995-9-1005
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Characterization of Isopyoverdin from Pseudomonas putida BTP1 and Its Relation to the Biogenetic Pathway Leading to Pyoverdins

Abstract: Pyoverdin type siderophores produced by six fluorescent Pseudomonas strains isolated from different rhizospheres were purified and characterized. The purified ferri-pyoverdins were tested for their ability to promote the growth of other strains grown under iron deficiency conditions. Only the one obtained from Pseudomonas putida BTP1 did not act as a growth promoter. The structure of the BTP1 siderophore was elucidated by spectroscopic methods and degradation studies. It turned out that it contains a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This is due to the quinoline chromophore found in all pyoverdins (2). Several pyoverdin precursors (2,4,16,31,32) or by-products (11,16,17) differ in chromophore structure and spectral characteristics. The spectral characteristics of the siderophore produced by P. syringae and P. viridiflava resemble the spectral characteristics of pyoverdins, but the siderophore differs from all of these molecules (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the quinoline chromophore found in all pyoverdins (2). Several pyoverdin precursors (2,4,16,31,32) or by-products (11,16,17) differ in chromophore structure and spectral characteristics. The spectral characteristics of the siderophore produced by P. syringae and P. viridiflava resemble the spectral characteristics of pyoverdins, but the siderophore differs from all of these molecules (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The strain has developed an efficient pyoverdine-mediated iron acquisition system (Jacques et al 1995;Ongena et al 2001); however, these chromopeptides do not play any role because previous results showed that pyoverdineenriched extracts failed to induce resistance (Ongena et al 2002). The strain has developed an efficient pyoverdine-mediated iron acquisition system (Jacques et al 1995;Ongena et al 2001); however, these chromopeptides do not play any role because previous results showed that pyoverdineenriched extracts failed to induce resistance (Ongena et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas putida BTP1, isolated from barley roots, originally was selected for its specific features regarding pyoverdinemediated iron transport (Jacques et al 1995;Ongena et al 2001). All strains were maintained on Pseudomonas agar F medium (KB; Becton, Dickinson, and Company, Le pont de Claix, France) at 4ºC before experimental use, and stored at -80ºC in cryotubes according to the manufacturer's recommendations (Microbank; Prolab Diagnostic, Richmond Hill, Canada) for long-term conservation.…”
Section: Microbial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromophore, identical for all the pyoverdines so far identified, is (lS)-5-amino-2,3-dihydro-8,9-dihydroxy-IH-pyrimido [I,2-a] quinoline-I-carboxylic (Michels et aI., 1991). One exception, however, has been recently described for a strain of P. putida which has a pyoverdine with a carboxylic group attached to the C 3 instead of the C 1 of the quinoline cyclic ring (Jacques et at., 1993(Jacques et at., , 1995.…”
Section: Purification Of Siderophoresmentioning
confidence: 99%